Faecal NIRS to assess the chemical composition and the nutritive value of dairy sheep diets - Decandia M.; Giovanetti V.; Boe F.; Scanu G.; Cabiddu A.; Molle G.; Cannas A.; Landau S. (Nutritional and foraging ecology of sheep and goats, 2009)
This study explored the value of faecal near infrared reflectance spectroscopy (NIRS) in predicting the chemical composition and the nutritive value of pelleted diets offered to dairy ewes. Reference data and faecal spectra were measured from three experiments in which dry, mid- and late-lactating Sarda dairy ewes were individually fed 8 different complete pelleted diets. The pelleted diets used featured different energy contents (1.2-1.9 Mcal/kg DM of NEL), NDF (23.9-51.9% DM) and fairly similar CP levels (17.5-19.8% DM). In each experiment, intake, chemical composition and in vivo digestibility of diets were measured. Individual faecal samples (n = 120) were collected, dried, milled and scanned between 1100-2500 nm in 2 nm increments using a Foss NIR-Systems 5000 monochromator spectrometer. Calibration equations were developed for predicting intake, dietary chemical composition on DM basis (CP, N fractions, NDF, ADF, ADL, NSC, WSC), in vivo digestibility coefficients (OMD, CPD, NDFD), and energy concentration (Mcal of NEL), by using the modified partial least squares procedure (MPLS). Values for R2 and the standard error of cross validation (SEC-V) were used as estimates of calibration equation prediction accuracy. Overall, the parameters of dietary chemical composition showed high R2 (>0.90) and low SECV, with best values for CP (R2 = 0.95, SECV = 0.24). Regarding the digestibility coefficients, OMD and NFCD presented the best values of R2 and SECV (0.90, 3.44; and 0.91, 2.51, respectively). Dietary energy concentration showed an R2 of 0.88 and SECV 0.09 Mcal/kg DM. This study confirmed the accuracy of the predictions based on faecal NIR spectra with reference to dietary chemical composition and, to a lesser extent, to its nutritive value.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)